2011
DOI: 10.3109/13880209.2010.527992
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic activity of two medicinal phytoextracts in somatic cells ofDrosophila melanogaster

Abstract: These results are in agreement with the uses of these phytoextracts in traditional medicine. Indeed, the lack of genotoxicity and the antimutagenic activity observed for both phytoextracts validates their use as a therapeutic modality to treat diabetic patients. Moreover, these extracts are suitable for consumption as teas and/or phytomedicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…and Cham. is a plant distributed in Mexico, where it is popularly known as "cola de caballo" [49] and traditionally used for the treatment of diabetes type 2 and kidney disease [14][15][16][17]. Regarding toxicological information, Téllez et al [49] have shown that extracts from E. myriochaetum aerial parts had no acute toxicity detected in Drosophila or in the human micronucleus test in vitro performed with cultured lymphocytes, emphasizing that this species is not genotoxic.…”
Section: Traditional Applications and Toxicological Informationmentioning
confidence: 99%
“…and Cham. is a plant distributed in Mexico, where it is popularly known as "cola de caballo" [49] and traditionally used for the treatment of diabetes type 2 and kidney disease [14][15][16][17]. Regarding toxicological information, Téllez et al [49] have shown that extracts from E. myriochaetum aerial parts had no acute toxicity detected in Drosophila or in the human micronucleus test in vitro performed with cultured lymphocytes, emphasizing that this species is not genotoxic.…”
Section: Traditional Applications and Toxicological Informationmentioning
confidence: 99%